Analisis Pengukuran Kualitas Marketplace Shopee Menggunakan Metode Six Sigma pada PT. Shopee Internasional Indonesia - Anisah Fadhilah; Tata Sutabri (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
This research employs the Six Sigma method using the DMAIC cycle (Define, Measure, Analyze, Improve, Control) to enhance the quality of Shopee’s services. Among the variables examined, significant results were found in the areas of delivery accuracy and application reliability. Based on the survey conducted, customer dissatisfaction reached 20% in delivery and 25% in application reliability. Through analysis, the root causes were identified and addressed by optimizing logistics and application stability. This research demonstrates that Six Sigma is effective in improving customer satisfaction and the quality of Shopee’s services.